Eksplorasi Puisi “Sumpah Bunga dan Putri Gunung” karya Wiko Antoni menjadi Musikalisasi Puisi Sinematik untuk pembelajaran Apresiasi Puisi di PBSI Universitas Merangin - Eriyani, Elfa; Antoni, Wiko; Diana, Ari (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
This activity highlights the integration of artificial intelligence in drama appreciation learning at PBSI Merangin University, with a focus on theatrical performances of poems by Wiko Antoni. Through an AI-based interactive approach, students are invited to explore the aesthetic meaning and cultural values in poetry, as well as develop creative expression through digital media. The results of the activity show that technology-based theatrical presentation is able to strengthen literary appreciation and enrich the learning experience.